Underground Activities and Labour Market Performance - Birthe Larsen; Ann-Sofie Kolm (Copenhagen Business School (CBS), Department of Economics, 2010)
This paper develops a general equilibrium search and matching model where an underground economy co-exists along with the formal part of the economy. In analyzing how tax and punishment policies aect labour market performance, we nd that punishment of infor- mal sector activities induce workers and rms to reallocate towards the formal sector. However, more importantly, we nd that this real- location tends to improve e ciency in search, reduce the overall wage pressure, and reduce actual unemployment.
hdl:10398/8209
Keywords: H24; H26; J64; 330; Tax evasion; Underground economy; matching; unemployment